The Impact Of Traffic On The Cluster Development In The Urban Area Of Bumi Serpong - Prasadja Ricardianto; Suhartono Suhartono; Susanty Handayani; Hadi Setyabudi Pramono; Abdullah Ade Suryobuwono; Femmy Sofie Schouten; Gusti Agung Eka Teja Kusuma (Jurnal Penelitian Sekolah Tinggi Transportasi Darat, 2025)
The main problems during the development of Cluster Boulevard De Latinos ABC in Bumi Serpong Damai area, Tangerang, were the emergences of new traffic rise and attraction at the access for in and out the Cluster ABC and rush activities around the area of Cluster ABC intersection. The main aim of this research was to conduct analyses of traffic performance modelling in the peak hours in the Cluster ABC and after the Cluster ABC has completely operated for five years. Traffic Impact Analysis was needed to predict whether the transportation infrastructures are under the influence of the development. The method of this research used a transportation modelling consisting of four steps, namely trip rise and attraction, trip distribution, mode selection, and traffic loading. Sampling technique used eight survey operators and three traffic experts. The result of this research was that there was a recommendation for mitigation that could be done by both the developer and the government. The key finding of the Traffic Impact Analysis was that to anticipate the increase of trip rise/attraction, then easy accessibility, reduction of distraction and safety risks for vehicles, as well as traffic management and engineering were needed for areas around the Cluster ABC